THE GUIDANCE IN READING THE QURAN AT ISHLAHUL UMMAH - Ernaliana (ite ngabdi, 2025)
The ability to read the Qur’an is an important skill learned by Muslims. However, not all can read the Qur’an with the correct recitation rules. Therefore, parents need to be firm in understanding and practicing the Qur’an. This service aims to assist TPQ Ishlahul Ummah students in studying the Qur’an according to the rules of Tajweed. This activity was attended by 20 students, with 15 women and five men. Each student has problems in learning Tajwid, including memorizing the letters of each Tajwid law. The service process is carried out through interviews, training, mentoring, and evaluation. The service results illustrate that implementing mentoring provides a separate motivational spirit for students and accelerates understanding the procedures for reading the Qur’an using recitation.